2022
DOI: 10.3390/cancers14122852
|View full text |Cite
|
Sign up to set email alerts
|

Medium to Long-Term Clinical Outcomes of Spinal Metastasectomy

Abstract: The prolonged survival of metastatic cancer patients highlights the importance of the local control of spinal metastases, which reduce patient performance status. This retrospective study examined the medium to long-term outcomes of spinal metastasectomy by evaluating 124 patients who underwent metastasectomy for isolated spinal metastases (2006–2018) with a postoperative follow-up for a minimum of 3 years. The findings present information on patient demographics (i.e., performance status, location of non-spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Studies with large cohorts have reported 1-year local control rates of 72-90% for spinal metastases from various types of primary cancers [28][29][30][31][32]. However, TES in large, experienced centers reportedly shows lower local recurrence rates than SBRT [33,34]. Furthermore, a recent study comparing TES and separation surgery with postoperative stereotactic radiosurgery reported that while both were efficient treatments for patients with isolated spinal metastases and spinal cord compression, local tumor control was better in the TES group [35].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with large cohorts have reported 1-year local control rates of 72-90% for spinal metastases from various types of primary cancers [28][29][30][31][32]. However, TES in large, experienced centers reportedly shows lower local recurrence rates than SBRT [33,34]. Furthermore, a recent study comparing TES and separation surgery with postoperative stereotactic radiosurgery reported that while both were efficient treatments for patients with isolated spinal metastases and spinal cord compression, local tumor control was better in the TES group [35].…”
Section: Discussionmentioning
confidence: 99%